Effect of 12 weeks of complex training on occupational activities, strength, and power in professional firefighters - Liu, Meng; Zhou, Kaixiang; Li, Bin; Guo, Zhenxiang; Chen, Yan; Miao, Guozhen; Zhou, Limingfei; Liu, Haoyang; Bao, Dapeng; Zhou, Junhong (Frontiers in Physiology, 2022)
Objective: This study examined the effects of 12-week complex training (CT) programs on professional firefighters' occupational activities, strength, and power. Methods: Thirty men professional firefighters were randomly assigned to the CT group (n=15) and control group (n=15). The CT group performed complex training and the control group completed resistance training (RT) twice a week over 12 weeks. The occupational activities, strength, and power were assessed at baseline and immediately after the intervention by measuring the performance of 100m load-bearing run (100m LR), 60m shoulder ladder run (60m SLR), 5×20m shuttle run (5×20m SR), 4th-floor climbing rope (4th-floor CR), countermovement jump with arm swing (CMJas), seated medicine-ball throw (SMT), one-repetition maximum bench press (1RM BP) and one-repetition maximum back squat (1RM BS). Results: The results showed that compared to RT, CT induced significantly greater improvements in 60m SLR (p = 0.007), 4th-floor CR (p = 0.020), CMJas (p =0.001), and SMT (p <0.001). Conclusion: These findings suggest that CT is a novel intervention with great promise of improving professional firefighters' occupational activities, strength, and power.